Tobacco addiction and smoking cessation in Austrian migrants: a cross-sectional study - Urban, Matthias (BMJ Open, 2015)
OBJECTIVE: Recent observations revealed substantial differences in smoking behaviour according to individuals’ migration background. However, smoking cessation strategies are rarely tailored on the basis of a migration background. We aimed to determine whether smoking behaviour and preferences for smoking cessation programmes differ between Austrian migrant smokers and Austrian smokers without a migration background. STUDY DESIGN: Cross-sectional study. SETTING: Recruitment and interview were performed at public places in Vienna, Austria. PARTICIPANTS: The 420 smokers included: 140 Bosnian, 140 Turkish migrant smokers of the first or second generation, as well as 140 Austrian smokers without a migration background. METHODS: We cross-sectionally assessed determinants of smoking behaviour and smoking cessation of every participant with a standardised questionnaire. PRIMARY OUTCOME MEASURE: The Fagerström Test for Nicotine Dependence. SECONDARY OUTCOME MEASURES: Determinants of smoking behaviour, willingness to quit smoking and smoking cessation. RESULTS: Nicotine addiction expressed via the Fagerström score was significantly higher in smokers with a migration background versus those without (Bosnian migrant smokers 4.7±2.5, Turkish migrant smokers 4.0±2.0, Austrian smokers without a migration background 3.4±2.3, p<0.0001). Bosnian and Turkish migrant smokers described a greater willingness to quit, but have had more previous cessation trials than Austrian smokers without a migration background, indicating an increased demand for cessation strategies in these study groups. They also participated in counselling programmes less often than Austrian smokers without a migration background. Finally, we found significant differences in preferences regarding smoking cessation programmes (ie, preferred location, service offered in another language besides German, and group rather than single counselling). CONCLUSIONS: We found significant differences in addictive behaviour and cessation patterns between smokers with and without a migration background. Our results indicate a strong demand for adjusting cessation programmes to the cultural background.